2021
DOI: 10.15252/embj.2021108439
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory phosphorylation site on Mec1 controls chromatin occupancy of RNA polymerases during replication stress

Abstract: Upon replication stress, budding yeast checkpoint kinase Mec1 ATR triggers the downregulation of transcription, thereby reducing the level of RNA polymerase (RNAP) on chromatin to facilitate replication fork progression. Here, we identify a hydroxyurea-induced phosphorylation site on Mec1, Mec1-S1991, that contributes to the eviction of RNAPII and RNAPIII during replication stress. The expression of the non-phosphorylatable mec1-S1991A mutant reduces replication fork progression genome-wide and compromises sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
(161 reference statements)
0
13
0
Order By: Relevance
“…Since Rfa1-S178 phosphorylation influences Mec1-Ddc2 association, we next asked if phosphorylation of Mec1-Ddc2 can also influences recruitment. Proteomic and genetic studies have demonstrated a number of phosphorylation sites in Mec1-Ddc2 that are important for function (Hustedt et al, 2015;Memisoglu et al, 2019). We found that purified Mec1-Ddc2 used in our previous studies is extensively phosphorylated and the majority of Ddc2's phosphorylation can be removed by phosphatase treatment (Supplementary Figure 3A).…”
Section: Phosphorylation Of the Ddc2 N-terminus Enhances Rpa Associationmentioning
confidence: 73%
See 3 more Smart Citations
“…Since Rfa1-S178 phosphorylation influences Mec1-Ddc2 association, we next asked if phosphorylation of Mec1-Ddc2 can also influences recruitment. Proteomic and genetic studies have demonstrated a number of phosphorylation sites in Mec1-Ddc2 that are important for function (Hustedt et al, 2015;Memisoglu et al, 2019). We found that purified Mec1-Ddc2 used in our previous studies is extensively phosphorylated and the majority of Ddc2's phosphorylation can be removed by phosphatase treatment (Supplementary Figure 3A).…”
Section: Phosphorylation Of the Ddc2 N-terminus Enhances Rpa Associationmentioning
confidence: 73%
“…Both Mec1 and Ddc2 are extensively phosphorylated in response to DNA damage, replication stress, and during the cell cycle, in a Mec1-dependent and -independent manner, and are suggested to regulate the checkpoint (Bastos de Oliveira et al, 2015;Hustedt et al, 2015;Memisoglu et al, 2019;Paciotti et al, 2000). Two characterised Ddc2 phosphosites, S173 and S182, have been shown to permanently arrest the cell cycle in response to a DSB when mutated to an alanine (Memisoglu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the differences between wild-type spindles and spindles that elongate precociously in the absence of the S-phase checkpoint have not been studied in detail. Additional MT- and kinetochore-associated factors, apart from the few already known, seem to be phosphorylated by the S-phase checkpoint [ 67 ], with an unknown outcome. An open issue is also the force balance that prevents metaphase spindles from elongating in absence of CEN duplication under replication stress.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%